International finance - Pilbeam, Keith (London Bloomsbury Academic, 2023)
International Finance is an established and internationally renowned introduction to the subject. It draws on recent events to provide comprehensive coverage of traditional theories and new research relating to the balance of payments, exchange rate determination and the international monetary system. This is the fifth edition of the text